IMPLEMENTATION MODEL OF THE NINE-YEAR COMPULSORY EDUCATION POLICY IN KEEROM REGENCY - Bau Anting (INJOSEDU: International Journal of Social and Education, 2026)
The nine-year compulsory education program is a strategic policy of the Indonesian government aimed at improving equitable access to basic education. In Keerom Regency, the implementation of this program still faces various challenges, including geographical constraints, limited educational infrastructure, and uneven distribution of teachers. This study aims to analyze the implementation of the nine-year compulsory education program by focusing on its effectiveness, obstacles, and the role of stakeholders. The research employs a descriptive qualitative approach using interviews, observations, and documentation. The results show that the program has been implemented but has not yet reached optimal outcomes. Major obstacles include economic limitations of the community, low awareness of the importance of education, and limited access to schools. In addition, the shortage of teachers and inadequate educational facilities affect the quality of learning. Although efforts have been made by the local government and schools, these have not fully addressed the needs of all communities. This study concludes that strong synergy between the government, community, and stakeholders is essential to improve the success of the program through adaptive and sustainable policies.